Job satisfaction among the employees of Radio Televisyen Malaysia (RTM) in marketing division / Mohd Ridzwan Misran - Misran, Mohd Ridzwan (Faculty of Business Management, 2006)
Job satisfaction is one of evaluation aspect in work behavior, which has been emphasized by all of the organizations to ensure the successful of organization's goal. In this research, the study is made towards Job Satisfaction among the employees of Radio Televisyen Malaysia (RTM) in Marketing Division. For the purpose of the study, exploratory research was deployed in order to identify factors that contribute to job satisfaction. Simple random sampling has been utilized with 48 respondents or the sample size. Self-administered questionnaire was used as the survey instrument besides interviews as the source of primary data. By using the analysis generated by SPSS (Statistical Package for the Social Science), results are analyzed and deduction being drawn. Looking at the result in data analysis and cross tabulation did hypothesis testing. Finally, the finding from this study conclude that most of the employees of RTM Marketing Division have moderate satisfaction with their job, and certain factors should be reviewed by RTM such as the rewards.